2019
DOI: 10.3389/feart.2019.00090
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Markov-Chain Monte Carlo Inversion of Low-Temperature Thermochronology Around Two 8 − 10 m Wide Columbia River Flood Basalt Dikes

Abstract: Flood basalt volcanism involves large volumes of magma emplaced into the crust and surface environment on geologically short timescales. The mechanics of flood basalt emplacement, including dynamics of the crustal magma transport system and the tempo of individual eruptions, are not well-constrained. Here we study two exhumed dikes from the Columbia River Flood Basalt province in northeast Oregon, USA, using apatite and zircon (U-Th)/He thermochronology to constrain dike emplacement histories. Sample transects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 59 publications
2
44
0
Order By: Relevance
“…If values for the parameters that are roughly constant are set, one can determine an approximate value for the initial crustal temperature that delimits the crack-meltback and crack-closing regimes. For example, scaling the solutions in Bruce and Huppert (1990) and adopting the reasonable constant values Δh f,m = 600 kJ/kg, Δh f,wr = 320 kJ/kg, c p = 950 J/kg K, η = 1000 Pa s, κ = 5 × 10 −7 m 2 /s, l = 10 km, Δp = 10 MPa, w i = 1.5 m, T m = 1250 °C, and T w = 1075 °C (Stebbins et al 1984;Lange and Carmichael 1990;Rubin 1995;Lange 1997;Petcovic and Dufek 2005;Giordano et al 2008;Pertermann et al 2008;Hofmeister et al 2009;Tikunoff and Spera 2014;Lesher and Spera 2015;Karlstrom et al 2019; see Online Resource 1 for more details), the transition between crack meltback and crack closing occurs roughly at the initial crustal temperature T ∞ = 280 °C.…”
Section: Thermophysical Considerationsmentioning
confidence: 99%
“…If values for the parameters that are roughly constant are set, one can determine an approximate value for the initial crustal temperature that delimits the crack-meltback and crack-closing regimes. For example, scaling the solutions in Bruce and Huppert (1990) and adopting the reasonable constant values Δh f,m = 600 kJ/kg, Δh f,wr = 320 kJ/kg, c p = 950 J/kg K, η = 1000 Pa s, κ = 5 × 10 −7 m 2 /s, l = 10 km, Δp = 10 MPa, w i = 1.5 m, T m = 1250 °C, and T w = 1075 °C (Stebbins et al 1984;Lange and Carmichael 1990;Rubin 1995;Lange 1997;Petcovic and Dufek 2005;Giordano et al 2008;Pertermann et al 2008;Hofmeister et al 2009;Tikunoff and Spera 2014;Lesher and Spera 2015;Karlstrom et al 2019; see Online Resource 1 for more details), the transition between crack meltback and crack closing occurs roughly at the initial crustal temperature T ∞ = 280 °C.…”
Section: Thermophysical Considerationsmentioning
confidence: 99%
“…Miocene volcanism is the most plausible explanation for the differential Miocene reheating. Several studies have shown how the emplacement of magmatic bodies can create partial resetting aureoles of the low-temperature thermochronological systems in the host rock; the size of these aureols is directly related to the duration of magmatism, the depth of emplacement, and the size of the intrusives (e.g., Karlstrom et al, 2019;Murray et al, 2018).…”
Section: /2019tc005887mentioning
confidence: 99%
“…1), which may have played a role in the small climatic impact of the CRB through heating and contact metamorphism of the crust 4,5,8 . While many of the dikes are buried under the thick CRB lavas, recent uplift of the province in the east has exposed inner workings of the crustal dike system (down to ~2 km depth [15][16][17], allowing an insight into dike-crust interactions [18][19][20] . This unique setting shows that dikes intruded into a variety of rock types including earlier erupted CRB lavas, granitic batholiths, and Paleozoic metasedimentary rocks that often contain organic-rich shale and carbonates.…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…Dikes range in thickness from 1 to >100 m, although the distribution strongly peaks at ~8 m, and larger structures likely record multiple reoccupations 15,16 . Based on the number of segments exhibiting partial melt in host rocks 16 , an estimated 3% of all known dikes served as feeders for lava flows and long-lived transport was probably highly localized along strike 19 . As they would have been potentially active for much longer, these feeder dikes likely caused larger degrees of thermal metamorphism and contact melting in country rocks than dead-end dikes that did not reach the surface [18][19][20] .…”
Section: Geologic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation